1955
DOI: 10.1021/ja01626a030
|View full text |Cite
|
Sign up to set email alerts
|

Peroxides. III.2 Structure of Aliphatic Peracids in Solution and in the Solid State. An Infrared, X-Ray Diffraction and Molecular Weight Study3

Abstract: Aliphatic Peracids in Solution and Solid State 5537 yielded a 2,4-dinitrophenylhydrazone, m.p. 122.5-123°, undepressed by admixture with an authentic sample.29 The 2,4-dinitrophenylhydrazone of isovaleraldehyde, m.p. 125.5-126°, strongly depressed the melting point of the above sample.Neopentyl Iodide with Bromine.-Neopentyl iodide (92.0 mmoles) reacted with bromine (93.3 mmoles) in petroleum ether for 1.25 hours at -78°and 1.5 hours at 0°g ave a very small amount (0.57 g., 4%) of an impure low boiling fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…There are several factors that could account for the insensitivity and small size of the observed primary DKIEs. It has been shown that peracids form intramolecular hydrogen-bonded species in dilute solutions of inert solvents, i.e., benzene, carbon tetrachloride, and dichloromethane . The H-bonding to the carbonyl oxygen of the peracid would have the effect of lowering the difference in the vibrational zero point energies for the O−H and O−D bonds in the ground state, which in turn lower the primary DKIE.…”
Section: Resultssupporting
confidence: 69%
“…There are several factors that could account for the insensitivity and small size of the observed primary DKIEs. It has been shown that peracids form intramolecular hydrogen-bonded species in dilute solutions of inert solvents, i.e., benzene, carbon tetrachloride, and dichloromethane . The H-bonding to the carbonyl oxygen of the peracid would have the effect of lowering the difference in the vibrational zero point energies for the O−H and O−D bonds in the ground state, which in turn lower the primary DKIE.…”
Section: Resultssupporting
confidence: 69%
“…However, the peak for the n→π* transition of the C=O bonds shifted to 284 nm for the NGO after oxidation. This red shift, which was attributed to inter-and intramolecular hydrogen bonding of peroxy acids [77], confirms the formation of peroxy acids from carboxylic acids on the NGO under the oxidation reaction conditions. The turnover number (TON) was calculated as a ratio of the amount of oxidized product to the mass of NGO.…”
Section: Characterization Of Ngo After Oxidationsupporting
confidence: 64%
“…However, some studies have related these two bands to the H-bonded association of the carboxylic acids and hydroxyl groups. 19,36 In addition, Swern et al 38 mentioned that the band at 1743 cm À1 is assigned to the formation of peracids. The band at 1711 cm À1 can be attributed to absorption of carboxylic acids 7,15,16 or to their dimer form.…”
Section: Resultsmentioning
confidence: 99%